The Theory of Linguistic Personality, Its Structural and System Characteristics - Mazhitayeva, Shara; D. Rapisheva, Zhanat; Y. Tuite, Yeldos; T. Nygmetova, Nurgul; Zhetpisbay, Sholpan; Saule, B. Karmanova (Opción, 2019)
The study of linguistic personality appeared in modern linguistics. The interest in a personal aspect of language learning has increased significantly not only in linguistics but also in all disciplines that are somehow related to language, such as psychology, philosophy, linguistic didactics. «Linguistic personality» is that core, defining the concept, around which the discussion of the most interesting problems is unfolding. The article contains a review of the works on the problems of the for- mation of the language personality. The purpose of the article is a comprehensive approach to the analysis of the lan- guage personality, revealing on the basis of discourse not only its psychological features but philosophical and worldview preconditions, ethnonational characteris- tics, social characteristics, historical and cultural sources. The main results are the identification of the problem of the language personality in modern linguistics, which is increasingly being considered in related sciences as an object of interdisciplinary research and in the aspect of the formation of a national language in which the subjective is transformed into an objective language. The article deals with the state of the theory of the language personality in linguistics, which causes an increased interest of modern linguistic scholars. Such key issues of studying the language personality are raised, such as the choice of the original term and the generic component, the establishment of the level of abstraction, the definition of structure.